Investigation of the structure and chemical composition of sediments of irrigators of the tower cooling tower - Veselovskaya, E. V.; Lazareva, E. A. (Izvestiâ vysših učebnyh zavedenij. Problemy ènergetiki, 2024)
RELEVANCE. The relevance of this study lies in the need to preserve their design cooling efficiency during the operation of cooling towers, as well as to prevent a decrease in the mechanical strength of sprinklers as a result of the formation of deposits that contribute to the deterioration of heat exchange conditions and strength characteristics of structural elements. OBJECT. Increasing the efficiency of heat transfer in the cooling processes of circulating water when using tower cooling towers at thermal power plants. METHODS. To achieve these goals, comprehensive studies of samples of circulating water and sediments formed on the sprinklers of tower cooling towers were carried out using classical methods of physico-chemical and elemental analyses, as well as sediment studies using X-ray diffraction analysis and electron microscopy. RESULTS. The relationship between the parameters of cooling water and the nature of sedimentsformed on the sprinklers, in particular the proportion of crystalline and non-organic ones, has been tracked. A method of highly effective pretreatment of source water with biodegradable biocidal reagents was considered in detail, since the existing disinfection method does not prevent the development of colonies of microorganisms on cooling tower sprinklers. The effectiveness of the use of the biodegradable THPS reagent, which is relatively safe for the environment in comparison with oxidizing biocides and classic bromine-based preparations, was studied in laboratory conditions. Laboratory studies were conducted in accordance with the interstate standard and included the determination of the total number of microorganisms and common colimorphic bacteria. Studies have shown that THPS treatment allows for the complete presence of microorganisms in cooling water samples. Biocidal treatment was carried out with reduced concentrations of the reagent (up to 30 mg/l) in a wide pH range (from 6.5 to 9.0 units). Experiments have shown high efficacy of the drug in a wide pH range even when it is dosed in small doses and a decrease in the effectiveness of this biocide when using increased concentrations of cationic flocculants used at the stage of pretreatment of river water.